Peningkatan Minat Dan Kemampuan Guru Dalam Pengembangan Indikator Dan Tujuan Pembelajaran Melalui Workshop Bimbingan Kelompok Di SDN Sumurbatu 14 Pagi - Suparmi, Suparmi (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
This study examines Based on the analysis of the Indicator document prepared by the teacher and interviews conducted by the school through staff and representatives, it turns out that the following problems are still found: 1). Teachers still experience difficulties in developing indicators (especially the components of learning objectives, learning materials, learning steps and assessments); coupled with the integration of cultural values ​​and national character in Indicator 2) Teachers' interest in compiling indicators is still low, because indicators can be purchased. The problems mentioned above each other are problems that must be solved or ways to solve them so that all teachers are interested, enthusiastic in compiling and developing indicators with no problems or obstacles in making them. With workshops (teachers) developing Indicators can improve skills in preparing and developing Indicators and can implement them in the learning process so as to improve the quality and learning outcomes.